PERAN GURU DALAM GERAKAN LITERASI SEKOLAH - Jariah, Siti; Marjani, Marjani (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Literacy is the ability to read and write. Even so, we can develop the notion of literacy further, because literacy which only consists of reading, writing and arithmetic is now not enough, but also must include reading and writing as mentioned earlier, numeracy literacy, scientific literacy, financial literacy, literacy information and communication as well as cultural literacy and citizenship. the purpose of literacy is to develop good character. developing a culture of literacy in schools and in the community, can increase knowledge possessed by reading various useful information, can increase one's understanding in taking essence of reading and filling time with literacy to make it more useful. The benefits of literacy are adding vocabulary, optimizing the work of the brain, adding new insights and information, improving interpersonal skills, sharpening oneself in capturing the meaning of information that is being read. a more useful literacy model is one that pays attention to praxis as the main one, because it starts from the praxis of the ability to create. For the more